A new magnetic flux leakage sensor based on open magnetizing method and its on-line automated structural health monitoring methodology. (November 2015) - Sun, Yanhua; Liu, Shiwei; Li, Rui; Ye, Zhijian; Kang, Yihua; Chen, Shaobo
Magnetic flux leakage sensors have been widely used for the structural health monitoring of ferrous materials (structural health monitoring). This article provides a new magnetic flux leakage sensor based on open magnetizing method. Starting with the traditional yoke magnetization method analyses, the provided open magnetizing method and testing principle are presented. Then, the comparative analyses between the two methods are conducted by finite element method, indicating that the open magnetizing method features less magnetic interaction force, more uniform magnetic flux density for swing scanning, simpler architectures, and more universal functions under the framework of similar magnetic excitation capability for defects. Furthermore, the sensor based on open magnetizing method is designed through optimization and the advantages for open magnetization method are confirmed by experiments with created sensors. Finally, on-line structural health monitoring methodology for the monitoring probe with "rigid" open–close and "free" tracking rope-swing functions is developed based on the proposed sensors. Meanwhile, experimental comparisons between the open and yoke probes for on-line automated monitoring are also conducted to successfully confirm the characters of smaller magnetic interaction force, less wear, and damage in contrast to the traditional on-line automated structural health monitoring technology. Additionally, the on-line automated magnetic flux leakage apparatus for the structural health monitoring of hoist wire ropes is developed and applied, which further confirms the good practicability for the structural health monitoring of hoist ropes under the poor working conditions.